2001
DOI: 10.1034/j.1399-302x.2001.160605.x
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin, amylase and mucin MUC5B and their relation to the oral microflora in hyposalivation of different origins

Abstract: There are several reasons for hyposalivation, each affecting the salivary composition in different ways. The aim of this study was to analyze and compare lactoferrin, amylase and mucin MUC5B in stimulated whole saliva collected from subjects with hyposalivation of different origins and to relate the results to the presence of some microbial species associated with oral disorders. Albumin was determined as a marker of serum leakage. The characteristic feature for subjects with radiation-induced hyposalivation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
2
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 42 publications
6
44
2
2
Order By: Relevance
“…An increase in the concentrations of sodium, chloride, calcium, and magnesium has been reported, while the concentration of potassium is only slightly affected (Ben-Aryeh et al, 1975;Dreizen et al, 1976;Anderson et al, 1981;Valdez et al, 1993). The concentrations of immunoproteins ( e.g., sIgA), lysozyme, and lactoferrin are increased (Brown et al, , 1978Makkonen et al, 1986;Valdez et al, 1993;Almståhl et al, 2001). The decrease in salivary flow rate, however, is greater than the increase in immunoprotein and lysozyme levels, and this results in a significant immunoprotein deficit.…”
Section: Salivary Glandsmentioning
confidence: 99%
“…An increase in the concentrations of sodium, chloride, calcium, and magnesium has been reported, while the concentration of potassium is only slightly affected (Ben-Aryeh et al, 1975;Dreizen et al, 1976;Anderson et al, 1981;Valdez et al, 1993). The concentrations of immunoproteins ( e.g., sIgA), lysozyme, and lactoferrin are increased (Brown et al, , 1978Makkonen et al, 1986;Valdez et al, 1993;Almståhl et al, 2001). The decrease in salivary flow rate, however, is greater than the increase in immunoprotein and lysozyme levels, and this results in a significant immunoprotein deficit.…”
Section: Salivary Glandsmentioning
confidence: 99%
“…Electrolytes are known to be secreted in the mouth by the salivary glands, although the exudation of serum from injured oral mucosa also contributes to electrolyte concentrations found in saliva. In patients with SS, an increase has been documented in the rate of salivary albumin due to inflammation of the salivary glands and to the leakage of serum through mucous membranes easily damaged by mechanical action; this could equally be the mechanism that promotes salivary electrolyte abnormalities in SS (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…As we noted a high correlation between the amount of daily alcohol consumption and salivary lactoferrin output (Table 2), ethanol may exert a directly toxic effect on lactoferrin secretion. It should be mentioned that salivary lactoferrin is secreted not only by intercalated duct cells of salivary gland tissue [7,13], but may also be released by activated neutrophils in damaged salivary glands, in gingivitis, or may be the result of blood leakage through inflamed or damaged oral mucosa [16,29]. It has been reported that six hours after acute ethanol (40%) consumption, damage had been caused to the oral mucosa epithelium with degeneration of the epithelial cells and leukocyte infiltration; after 12 hours, irreversible cytolysis or swelling of the intermediate layer cells of the oral mucosa developed, whereas 24-48 hours after acute alcohol consumption, disseminated ulcerations developed in the mouth [7,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in lactoferrin extracellular concentration is often regarded as an indicator of neutrophil activation [14,15]. A high lactoferrin concentration in saliva is often considered a marker of damage to the salivary glands, gingivitis, or leakage through inflamed or damaged oral mucosa, infiltrated by neutrophils [16]. As iron cations are an essential nutrient for certain types of bacteria, two binding sites for iron cations in lactoferrin provide its bacteriostatic effect by limiting availability of iron for bacteria such as Streptococcus mutans [17,18].…”
Section: Introductionmentioning
confidence: 99%